2018
DOI: 10.1002/ijc.32063
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal morphological and functional nature of bone marrow stromal cells provides preferential support for survival of acute myeloid leukemia cells

Abstract: Hematopoietic progenitors, residing in the bone marrow (BM) niche, are supported by mesenchymal stromal cells (MSCs). Cytogenetic and molecular aberrations in these progenitors lead to acute myeloid leukemia (AML). The BM-MSC role in leukemogenesis is not fully elucidated. In the current study, an ex-vivo system of patient's own stroma (POS), best mimicking the in-vivo BM niche, has been developed aiming to unravel interactions and crosstalk between MSCs and AML cells.POS derived from AML patients at diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…The extent to which leukemic blasts reprogram marrow stroma to generate a pro-leukemia environment [28] as compared with intrinsic differences between AML and ND MSCs leading to a preadipogenic phenotype is not certain [50]. Some studies have shown ongoing MSC changes in remission [18] and others have indicated persistence of an altered phenotype through all stages of disease [51].…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which leukemic blasts reprogram marrow stroma to generate a pro-leukemia environment [28] as compared with intrinsic differences between AML and ND MSCs leading to a preadipogenic phenotype is not certain [50]. Some studies have shown ongoing MSC changes in remission [18] and others have indicated persistence of an altered phenotype through all stages of disease [51].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular inhibitors such as CXCR4 inhibitors, VLA-4 inhibitors and E-selectin inhibitors are currently undergoing clinical trials (6,7). Immune cells and stromal cells are important components of the BM microenvironment, and are also the main influencing factors of leukemia development (8,9). The ESTIMATE program is a common method to explore the microenvironment of many tumors (10).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show increased cytokine and chemokine secretion from MSCs supporting AML cell proliferation and survival (Huang et al , ; Brenner et al , ; Yehudai‐Resheff et al , ). AKR1C1 knockdown altered the secretory cytokine profile of the AML‐MSCs, especially reducing the secretion of MCP‐1, IL‐6, IL‐8 and G‐CSF, which corresponded to reduced mRNA levels of all but IL‐8 .…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal MSCs in the leukaemic BM microenvironment drive the pathogenesis and progression of leukaemia (Corradi et al , ; Yehudai‐Resheff et al , ) by activating multiple pro‐survival pathways in the blasts (Zeng et al , ). Abdul‐Aziz et al () showed that the pro‐survival effect of AML‐MSCs on the AML blasts was mediated by the MIF/PKCβ/IL8 pathway, while Ruvolo et al () identified LGALS3 as a survival factor in the AML cells.…”
mentioning
confidence: 99%